Answer:
C=0.46 s⁻¹
Step-by-step explanation:
The general equation for the damped harmonic system given as
[tex]y=Xe^{-Ct}sin\omega t[/tex]
Where
A= Amplitude
[tex]A=Xe^{-Ct}[/tex]
C=Damping constant
Lets take at time t= t₁, A= K
And at time t= t₁+3 s ,A= K/4
[tex]A=Xe^{-Ct}[/tex]
[tex]K=Xe^{-Ct_1}[/tex] -----------1
[tex]\dfrac{K}{4}=Ke^{-C(t_1+3)}[/tex] -------------2
From equation 1 and 2
[tex]Xe^{-Ct_1}=Ke^{-C(t_1+3)}[/tex]
[tex]1=4e^{-3C}[/tex]
[tex]e^{3C}=4[/tex]
[tex]C=\dfrac{1}{3}\ln4[/tex]
C=0.46 s⁻¹